1990
DOI: 10.1152/ajpheart.1990.258.2.h347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidosis and alkalosis on hypoxic pulmonary vasoconstriction in dogs

Abstract: We studied the effects of metabolic and respiratory acidosis (pH 7.20) and alkalosis (pH 7.60) on pulmonary vascular tone in 32 pentobarbital-anesthetized dogs ventilated with hyperoxia (inspired oxygen fraction, FIO2 0.40) and with hypoxia (FIO2 0.10). Ventilation, pulmonary capillary wedge pressure (Ppw), and cardiac output (3 l.min-1.m-2) were maintained constant to prevent passive changes in pulmonary arterial pressure (Ppa). Metabolic acidosis and alkalosis were induced with HCl (2 mmol.kg-1.h-1) and NaHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 0 publications
3
52
3
Order By: Relevance
“…Supporting this hypothesis, manipulating pH i by inducing intracellular acidification inhibited, 61 while intracellular alkalinization enhanced, 61,84 HPV. However, these reports stand in contrast to other studies, in which HPV was attenuated by hypocapnic alkalosis [85][86][87][88][89] and enhanced by hypercapnic acidosis. [88][89][90] It should be noted, however, that the magnitude of the change in pH i under these conditions was not measured and could vary considerably from that in experiments where pH i was manipulated directly.…”
Section: Role Of Nhe1 In Acute Hypoxic Pulmonary Vasoconstriction (Hpv)contrasting
confidence: 95%
“…Supporting this hypothesis, manipulating pH i by inducing intracellular acidification inhibited, 61 while intracellular alkalinization enhanced, 61,84 HPV. However, these reports stand in contrast to other studies, in which HPV was attenuated by hypocapnic alkalosis [85][86][87][88][89] and enhanced by hypercapnic acidosis. [88][89][90] It should be noted, however, that the magnitude of the change in pH i under these conditions was not measured and could vary considerably from that in experiments where pH i was manipulated directly.…”
Section: Role Of Nhe1 In Acute Hypoxic Pulmonary Vasoconstriction (Hpv)contrasting
confidence: 95%
“…The rheological properties of dextran and a low haematocrit may explain the impairment of HPV in the dextran group. Metabolic situations, such as acidosis or alkalosis, could therefore modify the HPV response [22]. However, in the current study, no significant variation of pH and Pa,CO 2 were observed in the dextran group.…”
Section: Discussioncontrasting
confidence: 75%
“…Many investigators have attempted to assess the effects of HA or IA on vasoconstriction in the pulmonary circulation, mainly based on measurements of Ppa changes [16][17][18][19]. In the present study, however, a real-time confocal laser scanning luminescence optical microscope, which allows clear discrimination of individual microvessels from their neighbours, was applied [8].…”
Section: Critique Of Methodsmentioning
confidence: 99%